Cannabis use during pregnancy in the United States: The role of depression. (1st May 2020) - Goodwin, Renee D.; Zhu, Jiaqi; Heisler, Zoe; Metz, Torri D.; Wyka, Katarzyna; Wu, Melody; Das Eiden, Rina
Highlights: Cannabis use is more common among pregnant US women with vs. without depression. Over one in ten pregnant women with depression report past-month cannabis use. About one in four pregnant teens with depression reports past-month cannabis use. Depression-cannabis link is stronger when perceiving greater risk of cannabis use. Abstract: Background: Cannabis use is increasing in the United States. Prior work suggests tobacco use in pregnancy is much more common among those with depression. It is not known whether cannabis use is also more common among this especially vulnerable group. Identifying those at highest risk for cannabis use is required to direct prevention and intervention efforts. Methods: Data were drawn from the 2005–2018 National Survey on Drug Use and Health (NSDUH), an annual, cross-sectional sample of persons ages 12 and older representative of the US. The prevalence of past-30-day cannabis use by depression status (past-12-month) and by sociodemographic factors and perception of risk associated with cannabis use was estimated among pregnant women. Results: Cannabis use was significantly more common among pregnant women with, compared to without, depression (12.7 % vs. 3.7 %; odds ratio (OR) = 3.8 (95 % confidence interval 2.8, 5.0)). This was the case across all sociodemographic subgroups. The relationship between depression and cannabis use was significantly stronger among those who perceived moderate-great risk (OR = 6.9 (3.7, 13.0)) compared with no risk (OR = 1.6 (1.1, 2.4); Pint  = 0.0003) associated with regular use. Conclusions: Women with depression are more than three times more likely to use cannabis during pregnancy. Disparities in cannabis use among pregnant women by depression status appear to be echoing trends in tobacco use. Education about risks associated with cannabis use in pregnancy and prevention, akin to those for prenatal tobacco use, may be needed among pregnant women who are depressed to stem this increase and potentially growing disparity.